2017
DOI: 10.3168/jds.2016-12385
|View full text |Cite
|
Sign up to set email alerts
|

Within-herd prevalence thresholds for herd-level detection of mastitis pathogens using multiplex real-time PCR in bulk tank milk samples

Abstract: The objective of the study was to assess the value of quantitative multiplex real-time PCR examination of bulk tank milk samples for bovine mastitis pathogens as a tool for herd level diagnosis. Using a logistic regression model, this study is aimed at calculating the threshold level of the apparent within-herd prevalence as determined by quarter milk sample cultivation of all lactating cows, thus allowing the detection of a herd positive for a specific pathogen within certain probability levels. A total of 6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…DNA of CNS), apart from the detection target of BC. This comes in agreement with the findings of previous studies (Mahmmod et al ; Soltau et al ). One of the main different aspects between the qPCR analysis and BC is that qPCR analysis detects DNA, whereas BC detects only viable bacteria.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…DNA of CNS), apart from the detection target of BC. This comes in agreement with the findings of previous studies (Mahmmod et al ; Soltau et al ). One of the main different aspects between the qPCR analysis and BC is that qPCR analysis detects DNA, whereas BC detects only viable bacteria.…”
Section: Discussionsupporting
confidence: 94%
“…DNA‐based molecular diagnostics such as qPCR assays are increasingly implemented as a routine method for mastitis control programmes in the last few years in several countries (Nyman et al ; Timonen et al ; Soltau et al ). However, conventional bacterial culture (BC) is still regarded as the gold standard for mastitis diagnosis and implemented in routine diagnostic by most laboratories worldwide (Persson Waller ).…”
Section: Introductionmentioning
confidence: 99%
“…The recovery rates for S. uberis using culture-based methods alone has been reported to be low, with one study reporting the correct identification of S. uberis for 43% of the colonies obtained using modified Rambach media (n = 304 out of 706 putative colonies; Zadoks et al, 2005) and may have limitations for calculating the overall prevalence Assessment of the prevalence of Streptococcus uberis in dairy cow feces and implications for herd health of S. uberis carriage within a herd. Identification based on PCR has been used for the detection of S. uberis in mixed IMI (Gillespie et al, 1997;Ashraf et al, 2017;Soltau et al, 2017), as well as for detection of other bacteria within bovine feces, including Mycobacterium paratuberculosis (Collins et al, 1993) and Escherichia coli (Sharma, 2002). Given advances in availability of genome sequence information for S. uberis (Ward et al, 2009;Hossain et al, 2015), unique species-specific coding sequences have been identified and may be used in combination with culture-based detection methods to provide a specific tool for detection of S. uberis in herd prevalence studies.…”
Section: Introductionmentioning
confidence: 99%
“…uberis prevalence in dairy herds include implementation of hygiene measures, enhancement of the immune status of cows, and pathogen-specific treatment concepts (Krömker et al, 2014;Ruegg, 2014;Mansion-de Vries et al, 2015). Risk assessment based on monitoring data (Samson et al, 2016;Soltau et al, 2017;Taponen et al, 2017), the implementation of novel diagnostic tools (Archer et al, 2017;Leimbach and Krömker, 2018), improved strain characterization (Hossain et al, 2015;Davies et al, 2016;Vélez et al, 2017;MLST, 2018c), and vaccination (Collado et al, 2018) are contributing to improved epidemiological understanding of Strep. uberis IMI and new approaches to control and prevent infections.…”
Section: Introductionmentioning
confidence: 99%